Gaya Bahasa Sebagai Media Ekpresi di Lagu “Introvert” Karya Stand Here Alone - Yusuf Akbar Septian; Alif Muhammad Imami (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This article contains a discussion about the use of language style as a medium of expression in the lyrics of the song Karya Stand Here Alone with the title introvert, the selection of this song as a research material because in writing the lyrics using an interesting language style with a medium of expression that can make listeners, who especially have an introvert nature as if in accordance with their lives, in addition the selection of this song was chosen because it is one of the favorite songs of researchers who want to further analyze the meaning in the album, especially in the song entitled introvert. The purpose of this study is to analyze the use of language as a medium of expression in the song introvert. The study was conducted using a qualitative descriptive method that uses reading, listening and writing techniques, this study has the potential to be a reference for subsequent research.